Pola Korupsi di Perguruan Tinggi Swasta - Adhari, Agus (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2017)
Corruption is the act of an official or fiduciary person who unlawfully and wrongfully uses his station or character to procure some benefit for himself or for another person. Black’s Law Dictionary defines corruption largely more than just the object of corruption. Corruption is present in all categories, such: money corruption and authority. College, either state (public) college or private college have the same role in performance of education for the nation’s progress. College as the institution of education is not freed from corruption. This condition is caused by moral, culture and needs matter. There is the difference between corruption in state (public) college and private college. Corruption in state (public) college generally happens in markup budget area and abuse of power. While in private college, corruption is present when the academic transaction between lecture and student is happened. This difference is due to salary problem between lecture (government employees) and lecture in private college. State (public) college lecture’s salary is regulated (including number of salary) in separate law from private college lecture’s salary.